Cell type-specific transforming growth factor-β (TGF-β) signaling in the regulation of salivary gland fibrosis and regeneration - Kevin Muñoz Forti; Gary A. Weisman; Kimberly J. Jasmer (Elsevier, 2024)
Salivary gland damage and hypofunction result from various disorders, including autoimmune Sjögren's disease (SjD) and IgG4-related disease (IgG4-RD), as well as a side effect of radiotherapy for treating head and neck cancers. There are no therapeutic strategies to prevent the loss of salivary gland function in these disorders nor facilitate functional salivary gland regeneration. However, ongoing aquaporin-1 gene therapy trials to restore saliva flow show promise. To identify and develop novel therapeutic targets, we must better understand the cell-specific signaling processes involved in salivary gland regeneration. Transforming growth factor-β (TGF-β) signaling is essential to tissue fibrosis, a major endpoint in salivary gland degeneration, which develops in the salivary glands of patients with SjD, IgG4-RD, and radiation-induced damage. Though the deposition and remodeling of extracellular matrix proteins are essential to repair salivary gland damage, pathological fibrosis results in tissue hardening and chronic salivary gland dysfunction orchestrated by multiple cell types, including fibroblasts, myofibroblasts, endothelial cells, stromal cells, and lymphocytes, macrophages, and other immune cell populations. This review is focused on the role of TGF-β signaling in the development of salivary gland fibrosis and the potential for targeting TGF-β as a novel therapeutic approach to regenerate functional salivary glands. The studies presented highlight the divergent roles of TGF-β signaling in salivary gland development and dysfunction and illuminate specific cell populations in damaged or diseased salivary glands that mediate the effects of TGF-β. Overall, these studies strongly support the premise that blocking TGF-β signaling holds promise for the regeneration of functional salivary glands.